Aplicação do sistema de biosusceptometria AC para monitoramento de nanopartículas magnéticas na circulação sanguínea - Próspero, André Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the Biomagnetic research field, several methods have reported to study physiological parameters through the detection of magnetic fields generated by biological electrical currents or magnetic marker/tracers. Among such techniques, the Alternating Current Biosusceptometry (AC Biosusceptometry or ACB) system has been developed and refined with the main purpose of detecting and monitoring magnetic materials in biological systems (mainly in the gastrointestinal tract so far). With a pair of gradiometric pickup coils, the ACB system is able to obtain data related to local biological properties and also to study mechanical and physiological parameters, such as gastric emptying and contraction activity. This work presents an unprecedented study that applies the ACB system, associated to magnetic nanoparticles, as a new tool for preclinical characterization of magnetic nanoparticles. In vivo Experiments were performed in rat models to quantify the magnetic nanoparticles half-life in predefined time intervals, the particles arrival time in the animals heart and also the nanoparticles biodistribution. As an additional test, cardiovascular parameters were acquired during the particle intravenous administration, since these parameters directly influence the material half-life and biodistribution. The system presented good performance in all tests, with excellent reproducibility, sensitivity and temporal resolution. Also, these results suggest the ACB using as valuable evaluation method for magnetic nanoparticles preclinical characterization, in parameters as biodistribution and half-life in the bloodstream, since transient changes in mean arterial pressure and heart rate were found due to the magnetic nanoparticles intravenous administration. This work includes the development and characterization of a new low cost physics instrumentation, to subsidize circulatory system research, in small animals, and new nanostructured materials applications ...

As técnicas biomagnéticas possibilitam o estudo de diversos parâmetros fisiológicos através da detecção de campos magnéticos gerados por correntes biológicas ou por marcadores/traçadores magnéticos. Uma das técnicas utilizadas dentro desta vertente é a Biosusceptometria de Corrente Alternada (BAC). A técnica utiliza um sistema gradiométrico de bobinas para monitorar posição e concentração de materiais magnéticos em sistemas biológicos. A partir do monitoramento realizado pelo sistema, é possível obter dados relacionados com as propriedades biológicas locais e estabelecer parâmetros mecânico-fisiológicos, principalmente do trato gastrintestinal, como esvaziamento e atividade de contração gástrica. A proposta deste trabalho é inédita e consiste na aplicação do sistema BAC, associado à nanopartículas magnéticas utilizadas como traçadores, a fim de, futuramente, disponibilizar uma nova ferramenta para estudos de caracterização pré-clínica de nanopartículas magnéticas. Foram realizados experimentos com ratos para a quantificação do tempo de meia vida das nanopartículas magnéticas em intervalos de tempo pré definidos, além do tempo de chegada das partículas no coração dos animais, bem como sua biodistribuição. Como testes adicionais, foram realizadas quantificações de alterações em parâmetros cardiovasculares sobre a administração endovenosa das nanopartículas magnéticas, já que esses parâmetros cardiovasculares influenciam diretamente no tempo de meia vida e biodistribuição do material. O sistema demonstrou bom desempenho em todos os testes aplicados, apresentando excelente reprodutibilidade, sensibilidade e resolução temporal. Os resultados sugerem a utilização da BAC como método de avaliação de parâmetros de caraterização pré-clínica de nanopartículas magnéticas em organismos vivos, em avaliações de biodistribuição e tempo de meia vida das nanopartículas...
Keywords: Biosusceptometria de Corrente Alternada; Coração - Fisiologia; Nanopartículas; Biomagnetismo; Sangue - Circulação; Alternated Current Biosusceptometry